Pengaruh Pelatihan Siaga Bencana Gempa Bumi Terhadap Kesiapsiagaan Anak Usia Sekolah Dasar Dalam Menghadapi Bencana Gempa Bumi Di “Yayasan Hidayatul Mubtadiin Kediri - Sri Haryuni (coba, 2018)
Natural disaster preparedness in schools or madrassas important because of the hours of the lessons is a gathering place for students certainly have a high vulnerability. If it does not do disaster risk reduction efforts, the school or madrasah at high risk would cause many casualties and damage, quantitatively as much as 75% of schools in Indonesia are at risk of moderate to high hazard. The purpose of this study to determine whether there are effects of the earthquake disaster preparedness training to preparedness primary school age children in the face of the earthquake in the "Foundation Hidayatul Mubtadiin" of Kediri City.This research includes inferential study, the type of design used is cross sectional with a kind of pre experiment. The study design One group pretest posttest desighn. The population in the study sample were 24 respondents. The sampling technique using cluster random sampling. The variable in this study is the independent variable is the training of earthquake disaster preparedness and the dependent variable is the preparedness of primary school age children in the face of the earthquake.Data were analyzed using the Wilcoxon test match pair test by signing α = 0.05. Almost all of them elementary school age children are ready for as many as 10 (41.3%) and very prepared a total of 14 (58.3%) in the "Foundation Hidayatul Mubtadiin" Kediri Year 2016. From the statistical test by using the Wilcoxon test match test pair obtained value ρ = 0.000, then H0 rejected H1 accepted, meaning that there is Disaster Preparedness Training Effect of Earthquake Preparedness Against Childhood Elementary School in Earthquake Disaster in "Foundations Hidayatul Mubtadiin" of Kediri City.The results of this study recommends that the disaster management in order to better implement the importance of earthquake preparedness education in schools, can reduce the risk of a disaster at school with one of the programs to be disaster prepared schools.